1986
DOI: 10.1093/ageing/15.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Indices of Nutrition in the Elderly: A Study of Different Clinical Groups

Abstract: Anthropometric and biochemical indices of nutrition were measured in 450 elderly women in six groups spanning a wide range of physical dependency. Data from the group of active subjects living at home was used to derive reference ranges for elderly women. Although the index values of this group did not differ greatly from those seen in young subjects, there were large differences between this and some of the other elderly groups where the frequency of low values was as high as 50% for some parameters. Food int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 0 publications
3
46
1
Order By: Relevance
“…A number of studies show inadequate energy intake is common in older adults, especially for those living in institutions (15)(16)(17)(18). Our findings also found energy intake to be below the estimated average daily requirement (EAR).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A number of studies show inadequate energy intake is common in older adults, especially for those living in institutions (15)(16)(17)(18). Our findings also found energy intake to be below the estimated average daily requirement (EAR).…”
Section: Discussionsupporting
confidence: 54%
“…Older people who are underweight have an increased risk of morbidity and mortality (13) and compromised quality of life and functional ability (14). Data from other studies show 30-50% of nursing home-patients are underweight (15)(16)(17)(18), and obesity is rare among the institutionalized. The results of this study were similar to these previous findings, and in contrast to those of Baldelli et al (19), who found 93% of subjects were malnourished or at risk of malnourishment at the time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of malnutrition in institutionalised elderly has been estimated at 30 -70% (Asplund et al, 1981;Morgan et al, 1986;Rudman & Feller, 1989). In general, the causes of these deficiencies are threefold: (1) inadequate intake which might be caused by reduced macronutrient need, poor dietary habits, isolation, depression, dental or chewing problems, medication or dementia; (2) increased nutritional requirements due to fever, infection or dementia; and (3) losses of nutrients or reduced absorption, for instance protein loss from wounds, glycosuria, diarrhoea or medication (Mobarhan & Trumbore, 1991;Chernoff, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is also particularly common in old age 2 3. Good anthropometric reference data are therefore fundamental in assessing the nutritional state of elderly people as well as in studies quantifying the prevalence of malnutrition and screening for malnourished people.…”
Section: Introductionmentioning
confidence: 99%